Impatto dell’integrazione tra canale fisico e canale digitale sulle performance di vendita nei retailer locali - Curreli, Marco (Piccola Impresa / Small Business, 2015)
This study analyzes the effects of multi-channel sales strategy for small local retailer, limited to a circumscribed portion of the sales network . Through the method of the single case study, developed on a small grocery retailer of the Italian market, it enrich the main contributions in this field, in particular the model proposed by Cao and Li. The results tested on big retailer by Cao and Li are studied on small business of grocery retail, operating mainly at a local level.